Hip Abductor Muscle Strength In Patients With Avascular Necrosis of The Femoral Head - Niketa Patel; Jaykumar Soni (International Journal of Physiotherapy)
Background: Studies have reported that hip abductor muscle weakness is a common finding post-surgery in patients suffering from avascular necrosis of the femoral head. Hence, our main study aimed to estimate the hip abductor muscle strength in patients with avascular necrosis of the femoral head. Methods: This was a prospective observational study. The patients were recruited per the inclusion criteria of being more than 18 years of age and having unilateral avascular necrosis of the femoral head. Any patient with revision surgery or any other surgery in the hip was excluded. These subjects recruited for the study of their hip AVN were graded as per Ficat and Arlet classification by an experienced radiologist and underwent surgery. Following this, the hip abductor muscle strength of both lower limbs was measured using a sphygmomanometer. Their hip abductor muscle strength was measured during admission, after the surgery on postoperative day 03, and at discharge. All the recruited patients were given physiotherapy exercises based on strength, range of motion, and ambulation training from admission. Results: A total of 65 patients were recruited for the study. Fifty-four males and eleven females were part of the study. Independent t-test was used to find the differences between pre-surgery and post-surgery measurements. No statistically significant difference was observed in the hip abductor muscle strength from pre-surgery to post-surgery in the lower limbs. However, their mean values showed improvement in muscle strength from 97.43mmHg (pre-surgery) to 96.55mmHg (at the time of discharge). Conclusion: The hip abductor muscle plays a consequential role in hip surgery. Its recovery is significant for the better functional outcome. Physiotherapy following surgery improves the hip abductor muscle strength.